HUBUNGAN TINGKAT PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN BEROBAT PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS LAMPAHAN KABUPATEN BENER MERIAH - Maria Santiwi; Maulina Iriyanti; Nurlaely HS (Jurnal Ilmiah Cerebral Medika, 2026)
ABSTRACT Background: Hypertension is a complex condition where blood pressure is persistently above normal. Hypertension is called the silent killer because its symptoms are often without complaints. Treatment adherence of hypertensive patients is important because hypertension is a disease that cannot be cured but must always be controlled. Objective: This study aims to analyze the relationship between the level of knowledge and family support with adherence to hypertension treatment in the working area of the lampahan health center, bener meriah district. Methods: The research design used quantitative methods with cross sectional research type. Data were collected using a knowledge and family support questionnaire, while for compliance using the MMAS-8 (Morisky Medication 8-item Adherence Scale) questionnaire. The sample in this study was 80 people who were taken using purposive sampling technique. Data were analyzed using chi-square test. Results: Based on the results of the study, it was found that most respondents had sufficient knowledge about antihypertensive drugs, namely 35 people (43.8%), most respondents did not have family support in undergoing treatment, namely 43 people (53.7%). The statistical results of the square test test obtained (p value = 0.000). between the level of knowledge and treatment compliance, and also (p value = 0.000). This shows statistically that there is a significant relationship between the level of knowledge and family support with adherence to treatment of hypertensive patients in the working area of the lampahan health center, bener meriah district. Conclusion: The level of knowledge and family support has a relationship with adherence to treatment of hypertensive patients in the working area of the lampahan health center, Bener Meriah district. Keywords : Knowledge, Family Support, Adherence, Hypertension